Upaya Hukum Perusahaan Untuk Bangkit Dari Jeratan Tuntutan Kepailitan - Putri, Fallen Annisa Aji (Jurnal Hukum Statuta, 2023)
The bankruptcy of a company has widespread negative impacts, both locally and globally. Therefore, the existence of bankruptcy institutions is crucial in the business world. These institutions enable the orderly and fair settlement of debts when a company can no longer compete or is forced to exit the market.Bankruptcy occurs when a debtor fails to pay debts that have fallen due and can be demanded, indicating an inability to pay or insufficient income to settle debts. Bankruptcy aims to resolve debt issues rather than intentionally destroy a business. The principle of "commercial exit from financial distress" refers to the process by which financially unsustainable companies exit the market in an orderly manner. Facilitating the bankruptcy of debtors can help efficiently and fairly resolve debt, allowing creditors to receive payments according to the legal priorities of bankruptcy, and providing debtors with an opportunity to improve their finances and continue their business. To prevent bankruptcy, companies may file for a moratorium on debt payments to prepare a reorganization plan. However, unethical practices in commercial courts can harm creditors, underscoring the importance for the judiciary system to ensure transparent and fair bankruptcy processes.